Makna Minuman Tradisional (Moke) Ditinjau Dari Adat Masyarakat Sikka (Studi Kasus Di Desa Wairterang) - Hieronimus Chrisantus Soa; Danar Aswim; H.Rodja Abdul Natsir (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This study aims to find out the meaning of the traditional drink (Moke) in terms of the sikka indigenous people and what values ​​are contained in the traditional drink (Moke) for the sikka indigenous people. This study uses a qualitative method that is descriptive. The informants in this study were the customary leaders of the Wairterang village, community leaders in the Wairterang village and the Wairterang village community. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques include data reduction, data display and data verification. The results showed that moke has a meaning as a symbol of respect for ancestors, a symbol of brotherhood and cultural heritage. It has harmony values ​​and economic values ​​in the context of the custom of the Wairterang village community.